The dynamic interactions between cellular-molecular physiology and the environment - case studies in pathophysiology - how to exploit cellular-molecular evolution - Torday, John S. (Henry Stewart Talks, 2016)
Simplification of structure and function as reverse evolution, Chronic diseases & pathologies in different tissues and organs, Breakdown in cell-cell communication, Fibrosis & PPARɣ agonists, Sensing loss of homeostasis & cellular perturbations